The beginning of culturally renaissance in Arab Gulf region in the first half from 20th century (Journal of the College of Education for Women, 2019)
The present paper deal with the issue of the beginning of the culturallyrenaissance in emirates of Arab Gulf from 1914-1945 between tow world warhas been attracting the attention of academic about the developments in manyfields in the Arab Gulf at this time.The paper is divided into five sections. First section, deals with thegeographic importance for the Arab Gulf region. Second section, the economicsituations in the region before and after oil. The third section, talk for socialsituations, like population, tribe and tribes in society, and immigration. Thefourth section, deals with the factors of rise the culture and political in the ArabGulf before discovery of oil period. The five section, the culturally elements ofmodern education, library, culturally clubs and associations, press and papers.